Study of biodegradation of Poly(butylene adipate co-terephthalate) (PBAT) with exotic basil essential oil in anaerobic sludge (Research, Society and Development, 2022)
This paper aimed to evaluate the biodegradation of Poly(butylene adipate terephthalate) (PBAT) films and PBAT with exotic basil essential oil (OME), using the polyethylene film as a standard sample, for a period of 15 months by anaerobic digestion, in sludge from wastewater treatment plant. The evolution of the degradation of the films was quantified through the loss of mass and thickness over time and the viability of Acid Producing Bacteria, Heterotrophic Anaerobic Bacteria, Pseudomonas aeruginosa and Heterotrophic Aerobic Bacteria was also evaluated. As for the mass variation, polyethylene films showed no significant variation, while PBAT films, with and without exotic basil essential oil, showed variation. The thickness variation was statistically null for polyethylene and pure PBAT films, while PBAT/OME exhibited a small loss. Regarding the microorganisms present in the sludge, initially the sludge exhibited low microbial load and, over time, the growth of aerobic microorganisms in the medium was observed. At the end of the experiment, the presence of mostly Heterotrophic Aerobic Bacteria was verified. It was also possible to infer that the films of PBAT, as well as PBAT/OME suffered mass loss as an indication of the films degradation, over the time of exposure in the sludge, especially the film with OME additive.